2021
DOI: 10.1101/gr.272468.120
|View full text |Cite
|
Sign up to set email alerts
|

A flexible repertoire of transcription factor binding sites and a diversity threshold determines enhancer activity in embryonic stem cells

Abstract: Transcriptional enhancers are critical for development and phenotype evolution and are often mutated in disease contexts; however, even in well-studied cell types, the sequence code conferring enhancer activity remains unknown. To examine the enhancer regulatory code for pluripotent stem cells, we identified genomic regions with conserved binding of multiple transcription factors in mouse and human embryonic stem cells (ESCs). Examination of these regions revealed that they contain on average 12.6 conserved tr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 78 publications
(87 reference statements)
3
28
0
Order By: Relevance
“…Moreover, these enriched motifs typically belong to cell-type specific TFs that are not expressed in mESCs and are associated with differentiation. Consistent with our findings, a recent study which systematically analyzed the quantity and composition of TF motifs for mESC enhancers described a threshold for the minimal number of TF motifs required for enhancer activity (Singh et al ., 2021).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, these enriched motifs typically belong to cell-type specific TFs that are not expressed in mESCs and are associated with differentiation. Consistent with our findings, a recent study which systematically analyzed the quantity and composition of TF motifs for mESC enhancers described a threshold for the minimal number of TF motifs required for enhancer activity (Singh et al ., 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Low activity enhancers were also enriched for the motif of p53, which was recently found to bind “dormant” enhancers in mESCs that are located in inaccessible chromatin and become activated upon cellular stress or during reprogramming (Peng et al ., 2020). Another plausible explanation for increased activity levels of enhancers could be the absolute number of motifs per enhancer as well as on the diversity of these motifs (Singh et al ., 2021). Accordingly, we found that the high-activity enhancers, on average, contain more motifs (10.6 compared to 9.8 average motifs/enhancer, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it might be possible that these open but inactive regions become active in upon differentiation. Consistent with our findings, a recent study which systematically analyzed the quantity and composition of TF motifs for mESC enhancers described a threshold for the minimal number of TF motifs required for enhancer activity ( 61 ). Additionally, this finding of motifs adding synergistically to enhancer activity, once passing a threshold of minimal number of motifs, could explain the nature of super-enhancers, regulatory elements that are much larger in size (> 12 kb) and show much higher activity than regular enhancers.…”
Section: Discussionsupporting
confidence: 90%
“…Low activity enhancers were also enriched for the motif of p53, which was recently found to bind ‘dormant’ enhancers in mESCs that are located in inaccessible chromatin and become activated upon cellular stress or during reprogramming ( 45 ). Another plausible explanation for increased activity levels of enhancers could be the absolute number of motifs per enhancer as well as on the diversity of these motifs ( 61 ). Accordingly, we found that the high-activity enhancers, on average, contain more motifs (10.6 compared to 9.8 average motifs/enhancer, Figure 2D ) and were 14% larger than enhancers with low activity (385 bp versus 338 bp for low-activity enhancers, Figure 2E ).…”
Section: Resultsmentioning
confidence: 99%
“…As is known, the regulatory regions of the genome represent clusters of the binding sites for sequence-specific transcription factors (TFs). There, the interplay between these TFs and their binding sites ( cis -regulatory elements) as well as the interaction of TFs with one another and the coactivator and chromatin remodeling complexes orchestrate the dynamic and diverse genetic programs, thereby determining the tissue-specific gene expression, spatiotemporal specificity of gene activities during development, and the ability of genes to respond to different external signals [ 7 , 8 , 9 , 10 , 11 , 12 ]. Thus, thanks to the binding to their specific sites on DNA (transcription factor binding sites, TFBSs), TFs directly interpret the regulatory part of the genome, performing the first step in deciphering the DNA sequence [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%